Cellular Profile of Subfornical Organ Insulin Receptors in Mice - Han-Rae Kim; Jin-Kwon Jeong; Colin N. Young (Biomolecules)
Brain insulin receptor signaling is strongly implicated in cardiovascular and metabolic physiological regulation. In particular, we recently demonstrated that insulin receptors within the subfornical organ (SFO) play a tonic role in cardiovascular and metabolic regulation in mice. The SFO is a forebrain sensory circumventricular organ that regulates cardiometabolic homeostasis due to its direct exposure to the circulation and thus its ability to sense circulating factors, such as insulin. Previous work has demonstrated broad distribution of insulin receptor-expressing cells throughout the entire SFO, indirectly indicating insulin receptor expression in multiple cell types. Based on this, we sought to determine the cellular phenotypes that express insulin receptors within the SFO by combining immunohistochemistry with genetically modified reporter mouse models. Interestingly, SFO neurons, including both excitatory and inhibitory types, were the dominant cell site for insulin receptor expression, although a weak degree of insulin receptor expression was also detected in astrocytes. Moreover, SFO angiotensin type 1a receptor neurons also expressed insulin receptors. Collectively, these anatomical findings indicate the existence of potentially complex cellular networks within the SFO through which insulin signaling can influence physiology and further point to the SFO as a possible brain site for crosstalk between angiotensin-II and insulin.